*Phraseological issues in "exaggeration" in informal speech in Antioquia - García Zapata, Carlos (Íkala, Revista de Lenguaje y Cultura, 2000)
Contemporary linguistics is increasingly concerned with the analysis of everyday speech and the characteristic of regional speech today is the best place to begin such an analysis. Here the author examines certain phraseological aspects of hyperbolic Antioquian expressions which share a comparative and consecutive structure. Such aspects include, amongst others, the degree to which such expressions become part of spoken language, and the variants on each expression which further enrich oral communication.